A multi-agent architecture applying trust and reputation over unknown partners for live video distributed transcoding in open environments - Costa, Charles Antônio Nascimento (2022)
Dissertação (Mestrado em Informática) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, Brasília, 2021.